2018
DOI: 10.3389/fenvs.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Small-Scaled Differences in Micro-Aggregation on Physico-Chemical Parameters of Macroscopic Biopore Walls

Abstract: Macroscopic biopores, like earthworm burrows or channels which remain after a root decayed, act as preferential flow paths for water, gas, and heat transport processes, and viewing at agricultural production, as preferential elongation paths for plant roots. These processes result in intense alterations of the soil volume and its composition that surrounds the pores. The effects of these processes were analyzed at small-scale and physico-chemical soil parameters, i.e., relative oxygen diffusion coefficient (D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…The values of D s /D O are remarkably high, especially under field conditions with values that are comparable to sandy soils with high air-filled porosity (Moldrup et al, 2000); or with a well-structured, more silty soil (Mordhorst et al, 2017). Much lower values were found for European soils rich in clay (Uteau et al, 2013) or for biopore walls of these soils (Haas and Horn, 2018). The ratio D s /D O (Figure 4b) was significantly influenced by drainage to -6 kPa in the upper subsoil (FNP, t = 3.82; dF = 12; p ≤ 0.05) and in the lower part (NFNP and CP with t = 3.22; dF = 12; p ≤ 0.05 and t = 4.565; dF = 12; p ≤0.01; respectively).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The values of D s /D O are remarkably high, especially under field conditions with values that are comparable to sandy soils with high air-filled porosity (Moldrup et al, 2000); or with a well-structured, more silty soil (Mordhorst et al, 2017). Much lower values were found for European soils rich in clay (Uteau et al, 2013) or for biopore walls of these soils (Haas and Horn, 2018). The ratio D s /D O (Figure 4b) was significantly influenced by drainage to -6 kPa in the upper subsoil (FNP, t = 3.82; dF = 12; p ≤ 0.05) and in the lower part (NFNP and CP with t = 3.22; dF = 12; p ≤ 0.05 and t = 4.565; dF = 12; p ≤0.01; respectively).…”
Section: Resultsmentioning
confidence: 88%
“…For volcanic ash soil, this can be very relevant due to their shrinkage behavior (Dörner et al, 2010). The penetration of finer root hairs results in the creation of new and highly connected, lateral side pores, increasing the relative diffusion coefficient of the biopore-wall (Haas and Horn, 2018), and consequently, the exchange between biopores and the soil matrix. Furthermore, whenever a new surface is created, swelling pressures occur, leading to the formation of new cracks after the pressure is dissipated (Jayawardane and Greacen, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…An exception is the work of Stirzaker et al (1996) , who found that roots were more likely to occupy old root channels compared with artifical pores. In the field, the soil around biopores is likely to have distinct physico-chemical properties relative to the bulk soil ( Kautz et al , 2013 ; Haas and Horn, 2018 ). The biopores in the subsoil are less likely to be disturbed by tillage and, because they tend to have a vertical orientation, they are less sensitive to the effects of compaction and can remain intact for many years.…”
Section: Discussionmentioning
confidence: 99%
“…The density of macropore surfaces can potentially be affected by several factors: 1. Due to the compression of earthworms and roots, the outermost surface layer of biopores can be compacted (i.e., revealing higher bulk density values than the underlying soil matrix; Haas & Horn, 2018; Rogasik, Schrader, Onasch, Kiesel, & Gerke, 2014; Ruiz et al., 2015). 2.…”
Section: Discussionmentioning
confidence: 99%